The Academic Administration of Small Size Schools According to the Teacher Opinion in Rattanaburi District under the Surin Primary Educational Service Area Office 2 - Jaidee, Warintip; Sangngern, Supod; Suriyasookprasert, Pichai; Wisetsri, Suphap; Suriyasookprasert, Bancha (Rajapark Journal, 2024)
The objectives of this research were 1) to study the academic administration of small-size schools in Rattanaburi District under the Surin Primary Educational Service Area Office 2, 2) to compare the academic administration of small-size schools in Rattanaburi District under the Surin Primary Educational Service Area Office 2, classified by educational level and knowledge worker positions of the respondents. The samples consisted of 148 teachers from the small schools in Rattanaburi District, which were obtained through simple sampling. The instrument used for data collection was a 5-level estimation scale questionnaire with a confidence value equivalent to 0.962. The statistics used in data analysis were percentage, mean, and standard deviation. The hypothesis test uses the t-test and F-test. It was found that: 1) The academic administration of small-size schools, based on the teacher opinion in Rattanaburi District, overall is at a high level. 2) The academic administration of small-size schools based on teachers’ feedback in Rattanaburi District was statistically significantly different according to the overall level of education of the respondents at the level of .05.